Lund University Cardiac Assist System Induced Liver Laceration and Anterior Cord Infarction After Cardiac Arrest: A Case Report. Issue 3 (1st February 2020) - Drew, Thomas; Blackstock, Adam; Aron, Jonathan
Abstract : We describe a hepatic laceration and subsequent anterior spinal artery syndrome in a 21-year-old man, secondary to prolonged cardiopulmonary resuscitation with a Lund University Cardiac Assist System (LUCAS2) mechanical cardiac compression device. We briefly review the current literature pertaining to hepatic injury from trauma due to cardiopulmonary resuscitation. The etiology of the anterior spinal artery syndrome in this patient is discussed. This case highlights that intra-abdominal causes of hypotension should be considered in patients after a prolonged resuscitation attempt. Extending focused cardiac ultrasound to exclude intra-abdominal free fluid should be routinely considered in these patients.